The Influence of English IQ On Students’ Speaking Performance For Marketing Outcomes - Khairullah, Mohammad Noor; Ariyono, Kurniawan Yunus (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
One principal use of language is to communicate meaning, but it is also to establish and maintain relationship. There are the different purposes in speaking skill and the implementation on speaking in activity. First, speaking for casual conversation, have purposes may be to make social contact with people, to establish rapport. Speaking in discussion with someone, the purposes may be to seek or express opinions, to persuade someone about something or to clarify information. Intelligence is very important to know how far the students receive the material of lesson and everything which they learn. English Intelligence contributes no more than 20% in determining the success of someone in their life, while the other 80% is filled by other factors.This study is intended to know the correlation of students’ English Intelligence correlate with speaking achievement of students at the first semester in the English for Business lecturing of Management Department Widya Gama Lumajang in Academic Year 2024/2025. The research design of this study is correlation design since it used statistical measurement for the data analysis to describe the relationship between two variables. The data is analyzed by using Pearson-Product Moment formula. The population of this research is all of students at the first semester in English for Business class, they are divided into 10 classes. The result of this study is the correlation of students’ English Intelligent on students’ speaking performance for marketing outcomes is weak correlation with coefficient correlation 0.220.ABSTRAKSalah satu penggunaan utama bahasa adalah untuk mengkomunikasikan makna, tetapi juga untuk membangun dan memelihara hubungan. Ada beberapa tujuan yang berbeda dalam keterampilan berbicara dan penerapannya dalam aktivitas berbicara. Pertama, berbicara untuk percakapan biasa, memiliki tujuan untuk melakukan kontak sosial dengan orang lain, untuk membangun hubungan. Berbicara dalam diskusi dengan seseorang, tujuannya mungkin untuk mencari atau mengungkapkan pendapat, membujuk seseorang tentang sesuatu atau untuk mengklarifikasi informasi. Kecerdasan sangat penting untuk mengetahui sejauh mana siswa menerima materi pelajaran dan segala sesuatu yang mereka pelajari. Kecerdasan Bahasa Inggris memberikan kontribusi tidak lebih dari 20% dalam menentukan keberhasilan seseorang dalam kehidupannya, sedangkan 80% lainnya diisi oleh faktor-faktor lain. Penelitian ini bertujuan untuk mengetahui korelasi antara kecerdasan Bahasa Inggris mahasiswa dengan prestasi berbicara mahasiswa pada semester pertama dalam perkuliahan English for Business di Jurusan Manajemen Widya Gama Lumajang Tahun Ajaran 2024/2025. Desain penelitian dari penelitian ini adalah desain korelasi karena menggunakan pengukuran statistik untuk analisis data untuk menggambarkan hubungan antara dua variabel. Data dianalisis dengan menggunakan rumus Pearson-Product Moment. Populasi dari penelitian ini adalah seluruh mahasiswa semester pertama di kelas Bahasa Inggris untuk Bisnis, yang terbagi dalam 10 kelas. Hasil dari penelitian ini adalah korelasi antara kecerdasan bahasa Inggris mahasiswa dengan kinerja berbicara mahasiswa untuk hasil pemasaran adalah korelasi yang lemah dengan koefisien korelasi sebesar 0,220.